1999
DOI: 10.1111/j.1469-7793.1999.0719u.x
|View full text |Cite
|
Sign up to set email alerts
|

Incremental conductance levels of GABAA receptors in dopaminergic neurones of the rat substantia nigra pars compacta

Abstract: Molecular and biophysical properties of GABAA receptors of dopaminergic (DA) neurones of the pars compacta of the rat substantia nigra were studied in slices and after acute dissociation. Single‐cell reverse transcriptase‐multiplex polymerase chain reaction confirmed that DA neurones contained mRNAs encoding for the α3 subunit of the GABAA receptor, but further showed the presence of α4 subunit mRNAs. α2, β1 and γ1 subunit mRNAs were never detected. Overall, DA neurones present a pattern of expression of GABAA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 49 publications
3
30
0
Order By: Relevance
“…One study reported the detection of GABA A ␣1 subunit protein in dopamine neurons in humans (Petri et al, 2002), whereas two studies using single-cell RT-PCR in rodents failed to confirm this finding (Guyon et al, 1999;Okada et al, 2004), suggesting a minimal, if any, expression of ␣1 subunit in these cells. We investigated GABA neurotransmission in dopamine neurons using patch-clamp electrophysiology in acute slices.…”
Section: Duration Of Inhibition: a Driving Force For Neuronal Plasticitymentioning
confidence: 95%
“…One study reported the detection of GABA A ␣1 subunit protein in dopamine neurons in humans (Petri et al, 2002), whereas two studies using single-cell RT-PCR in rodents failed to confirm this finding (Guyon et al, 1999;Okada et al, 2004), suggesting a minimal, if any, expression of ␣1 subunit in these cells. We investigated GABA neurotransmission in dopamine neurons using patch-clamp electrophysiology in acute slices.…”
Section: Duration Of Inhibition: a Driving Force For Neuronal Plasticitymentioning
confidence: 95%
“…Recent studies have shown that synaptic plasticity may enhance synaptically triggered burst firing and therefore underlie the acquisition of the burst response to a reward-predicting stimulus (Harnett et al 2009). Although changes in plasticity can be effected within minutes, changes in the balance between excitatory and inhibitory inputs are capable of modulating bursts quicker.…”
Section: Tipping the Scales: Generating Pauses And Burstsmentioning
confidence: 99%
“…Using a GABA A receptor time constant of 6 ms (;Brancucci et al 2004), a single channel conductance of 5-30 pS (⌬g; Guyon et al 1999;Macdonald and Olsen 1994), and a 50 Hz input rate (F), we calculate that 887-5,330 GABA A receptors must be activated by globus pallidus and substantia nigra pars reticulata inputs to achieve the 8 nS steady-state conductance (g ss ) used in the balanced configuration in Fig. 1D (g (Fujiyama et al 2002) times 2.5 GABA A receptors per gold particle (Nusser et al 1997)], this corresponds to a minimum ϳ1-8% of the total GABAergic synapses onto an SNc neuron (ϳ5,600 GABAergic synapses total; Henny et al 2009).…”
Section: High Conductance State Of the Dopaminergic Neuronmentioning
confidence: 99%
“…Recombinant GABA A receptors are different from native GABA A receptors in that they never display single channel conductances greater than 40 pS, nor do drugs modulate their conductance, properties we and others have described for native nonsynaptic (extrasynaptic) GABA A receptors (3)(4)(5)(6)(7)(8). We have, however, been able to mimic the behavior exhibited by neuronal extrasynaptic GABA A receptors in a recombinant system and change the dispersion of receptors in the membrane simply by co-expressing the trafficking protein GABARAP with GABA A receptors (9).…”
mentioning
confidence: 99%